Influence Of Job Enlargement On Employee Performance In The Railway Industry In Kenya - Gichuki, Mary Mwihaki; Munjuri, Mercy Gacheri (Archives of Business Research, 2018)
There are numerous factors that affect the level of job satisfaction and this is highly influenced by the design and the nature of tasks assigned to the employees. The purpose of this study was to determine the influence of job enlargement on the performance of employees in the railway industry in Kenya. The study was done in one of the major railway companies in Kenya. A descriptive survey research design was adopted and the target population comprised all the 2000 employees of the railway company, out of which a sample of 400 employees was selected using systematic random sampling technique. Primary data was collected using structured questionnaires. Descriptive statistics and regression analysis approaches were employed in data analysis. The findings revealed that job enlargement contributed positively in enhancing employee performance. Regression results showed that task structuring and work arrangement resulted into increased employee performance while work meaningfulness was inversely linked to employee performance. The researcher recommends that the government should institute training and development programs to nurture employee knowledge and skills on how employee duties can be structured to boost their understanding of organizational processes and procedures. Organizations should consider implementing flexible structures that accommodate environmental changes and as such employees can identify tasks more efficiently and achieve their set targets. Future researchers can replicate this study in the private sector to establish whether the results realized under this study would hold.